Some remarkable new Neotropical treehoppers (Hemiptera: Cicadomorpha: Membracidae) - Dietrich, C. H. (Zootaxa, 2008)
The new Neotropical treehopper genera Smergotomia, based on S. clairae, new species, from Ecuador, and Braxtonota, based on B. enigmata, new species, from Puerto Rico are described and illustrated. Despite lacking a posterior pronotal process, Smergotomia appears to be most closely related to Smerdalea Fowler based on the forewing venation and male genitalia, but the subfamily and tribal placement of these two genera is uncertain. Braxtonota appears to be related to the two membracid tribes that are endemic to the Caribbean, but lacks the extra hind femoral cucullate setae diagnostic for Monobelini and the large teeth on the second valvulae diagnostic for Nessorhinini. It is provisionally placed in Monobelini. Smerdalea veracruzensis, new species from Mexico, with a pronotum considerably less ornate than its congeners, is also described and illustrated and a key to species of Smerdalea is provided.